2000
DOI: 10.1001/archinte.160.5.621
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Blocking Agents in Heart Failure

Abstract: In patients with heart failure, beta-blockers reduce total and cardiovascular mortality at the expense of a decrease in mortality due to pump failure and sudden death. The magnitude of the benefit is similar in patients with IHD and in those with non-IHD. Vasodilating beta-blockers have a greater effect on overall mortality than nonvasodilating agents, particularly in patients with non-IHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(15 citation statements)
references
References 49 publications
(113 reference statements)
1
14
0
Order By: Relevance
“…Thus, during local or global cardiac ischemia, the condition will be comparable to that induced by tyramine-stimulation, and inhibition of β 1 AR-mediated vasodilatation may disturb cardiac perfusion, particularly if combined with losartan, without having the desired effect on cardiac work load and cardiac energy consumption. This may explain why vasodilatory β-blockers reduced overall mortality with a greater effect than non-vasodilatory β-blockers such as atenolol (33). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, during local or global cardiac ischemia, the condition will be comparable to that induced by tyramine-stimulation, and inhibition of β 1 AR-mediated vasodilatation may disturb cardiac perfusion, particularly if combined with losartan, without having the desired effect on cardiac work load and cardiac energy consumption. This may explain why vasodilatory β-blockers reduced overall mortality with a greater effect than non-vasodilatory β-blockers such as atenolol (33). …”
Section: Discussionmentioning
confidence: 99%
“…Though, the number of clinical trials that classified such patients accounts for <22% in our meta-analysis. Similarly, study of Bonet et al [43] reported no difference in mortality benefits among ischemic and non-ischemic heart disease and proposed greater benefit of vasodilating beta-blockers compared with the non-vasodilating agents particularly in patients with non-ischemic cardiomyopathy and attributed mortality benefits to significant reduction of pump failure and sudden death. Briefly, previous studies whether had not evaluated overall reduction of beta-blockers in the prevention of sudden cardiac death or need to be updated such as the studies of Bonet et al [43] and Heidenreich et al [40] as several recent and large randomized clinical trials have been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…The use of concomitant therapy with beta-adrenergic antagonists, a class of drugs with proven efficacy in the treatment of heart failure [34], [35], varied widely across trials, but was far from optimal. In only three trials [24], [28], [29] more than 50% of patients were taking beta-adrenergic antagonists in addition to ACE inhibitors and in only one small trial >90% were taking beta-adrenergic antagonists [29].…”
Section: Discussionmentioning
confidence: 99%